Price premium effect, supply contracts and strategic decision making under environmental considerations. Issue 5 (11th June 2019) - Ramani, Vinay; Swami, Sanjeev; Ghosh, Debabrata
Abstract : Purpose: The purpose of this paper is to study the impact of collaboration between supply chain entities in a dyadic setting where the manufacturer invests in greening and technology adoption effort leading to a price premium effect for the supply chain players. Design/methodology/approach: The paper uses game theoretic approach to analyze the model of inter-firm interaction in a vertical channel setting consisting of a retailer and manufacturer. The paper studies strategic decisions of the channel members in a decentralized and centralized structure and extends this to decision making under contractual settings. Findings: A two-part tariff completely coordinates the green supply chain, while a cost sharing and revenue sharing contract only achieve partial coordination. Nevertheless, a cost sharing, as well as a revenue sharing contract, increases the greening and technological adoption effort by the manufacturer while yielding the supply chain members a strictly larger profit. Furthermore, a revenue sharing contract in comparison to a cost sharing contract, leads to a larger greening and technological adoption effort by the manufacturer, lower wholesale and retail prices and a strictly larger profit for both the manufacturer and the retailer. Originality/value: This paper contributes to the green supply chain pricing, technology and contract literature considering strategic interactions between a manufacturer and retailer in a supply chain under price premium effects of greening activities and technological advancements.